1983
DOI: 10.1055/s-2007-1022016
|View full text |Cite
|
Sign up to set email alerts
|

Functional Surgery of Bullous Emphysema

Abstract: Multiple large and small emphysematous bullae were resected in 27 patients with chronic obstructive lung disease (COLD). Twenty-two patients were operated on one side, and 5 patients underwent bilateral consecutive operations. Twenty-five patients were male, 2 female, and they were between 22 and 67 years old (mean 49.5 years). All patients had a follow-up examination between 3 and 48 months postoperatively. As operative techniques, resection by means of a clamp, plication of cysts according to Nissen, resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
2
Order By: Relevance
“…In one study (1) even an improvement of pulmonary hemodynamics after the procedure was reported. In contrast, in the case of reduction pneumoplasty for giant bullous emphysema, the basis of lung volume reduction surgery (LVRS) is to withdraw functionless yet nonbullous lung tissue in order to improve the lung's mechanical properties by increasing its elastic recoil (2)(3)(4) and to increase diaphragmatic motion, thus lowering the work of breathing (5)(6)(7)(8).…”
mentioning
confidence: 94%
“…In one study (1) even an improvement of pulmonary hemodynamics after the procedure was reported. In contrast, in the case of reduction pneumoplasty for giant bullous emphysema, the basis of lung volume reduction surgery (LVRS) is to withdraw functionless yet nonbullous lung tissue in order to improve the lung's mechanical properties by increasing its elastic recoil (2)(3)(4) and to increase diaphragmatic motion, thus lowering the work of breathing (5)(6)(7)(8).…”
mentioning
confidence: 94%
“…Among the different surgical techniques that have been employed to treat emphysematous bullae, bullectomy with resection or plication of the bullae carried out through thoracotomy [4][5][6] or even median sternotomy for one-stage bilateral treatment [7] has been frequently employed to eliminate these space-occupying lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In Fällen von einzelnen Riesenbullae, voluminösen, einen ganzen Lappen einnehmenden Bullae oder mehreren, die Lappen zerstörenden, paraseptal aufgereihten Bullae scheint auch eher ein chirurgisches Vorgehen indiziert [23]. Gerade bei Patienten mit einem sekundären Spontanpneumothoraxmeist erstversorgt mit einer Thoraxdrainagewird häufig eine Talkumpleurodese empfohlen [24].…”
Section: Bullöses Oder Ausgeprägtes Paraseptales Emphysemunclassified
“…Im Falle einer erfolgreichen kontralateralen BLVR können die Ventile in situ gelassen werden, um eine er-neute plötzliche Zunahme der Überblähung nach der Entfernung zu vermeiden. Bei entsprechender Zielzone auf der Gegenseite und Erfüllung der Voraussetzungen für eine BLVR können die Patienten auch von einer erneuten BLVR der Gegenseite profitieren, wie auch Fallbeispiel 5 zeigt [23,27].…”
Section: Rezidiv Von Symptomen Nach Einer Stattgehabten Lungenvolumen...unclassified